Restoring lions Panthera leo to northern KwaZulu-Natal, South Africa: short-term biological and technical success but equivocal long-term conservation - Hunter, L.T.B.; Pretorius, K.; Carlisle, L. C.; Rickelton, M.; Walker, C.; Slotow, R.; Skinner, J. D. (Oryx, 2007)
The success of efforts to re-establish mammalian carnivores within their former range is dependent on three key factors: methodological considerations, the biological requirements of the target species, and the involvement of local human communities for whom large carnivores pose a threat. We consider the role of these factors in the first 13 years of an effort to re-establish wild lions in northern KwaZulu-Natal Province, South Africa. We employed soft-release methods to mitigate the characteristic problems associated with restoration of large carnivores. A pre-release captivity period facilitated acclimatization of reintroduced lions and promoted long-term bonding of unfamiliar individuals into cohesive groups. All individuals remained in the release area and established enduring, stable home ranges. Reintroduced lions successfully reproduced and raised 78% of their cubs to independence. Human activity was the cause of all post-release mortality. Despite rapid population growth and the re-establishment of the species at Phinda Private Game Reserve, the population is small and isolated with little prospect for re-colonizing additional areas where the species has been extirpated, or for connecting with other isolated lion populations in the region. Accordingly, although we essentially overcame the short-term technical and biological challenges facing lion reintroduction, the long-term value of the Phinda population for addressing the conservation issues facing the species remains equivocal.